Antibacterial and antihypertensive properties of crude extract of in vitro callus culture of muskmelon (cucumis melo l.) - Nurul Ashikin, Abdul Karim (2014)
Muskmelon or Cucumis melo L. is one of the melon families that are widely consumed in many countries. The plant’s ability to adapt to many climate condition makes it available in the market throughout the year. Phytochemicals is one of the important components in plant. In this study, the methanolic extract of callus from muskmelon were studied and tested for antihypertensive and antibacterial activities. The explants were chosen from plant part; leaf, stem and fruit according to the highest total phenolic content where the leaf part showed the highest content. The calli were induced from the explant in the medium with plant growth regulators (PGRs) at a concentration ranging from 0 to 2.0 mg/L. Murashige and Skoog (MS) medium supplemented with PGRs: Zeatin (Z) 1.5 mg/L with 2,4-Dichlorophenoxyaceticacid (2,4-D) 1.5 mg/L, 6-Benzylaminopurine (BAP) 0.5 mg/L with 2,4D 1.5 mg/L, Indole-3-Butyricacid (IBA) alone 1.5 mg/L and 2,4-D alone 1.5 mg/L have successfully induced viable callus for extraction. The four weeks old calli were chosen for methanolic extraction because of its high total phenolic (TP) and total flavonoid (TF) content. It was found that C4 contained the highest amount of TP and C3 showed highest TF. The methanolic extracts were tested for antibacterial and antihypertensive activity. Three Gram Negative bacteria Escherichia coli (ATCC 10536), Salmonella typhi (ATCC 1331), Pseudomonas aeroginosa (ATCC 1542), and three Gram Positive bacteria Enterococcus faecalis (ATCC 14506), Staphylococcus aureus (ATCC baa1026), , and Bacillus subtilis (ATCC 11774), were used for antibacterial test in this study. Only the C3 and C4 extracts were able to inhibit bacterial growth as measured by inhibition zone and minimal inhibitory concentration. While in antihypertensive test, the C4 extract showed the highest inhibition rate (70.32%) against angiotensin converting enzyme and the extract from C3 showed the lowest (50.78 %) inhibition. The phytochemical profile of the extracts was determined by HPLC where the presence of phenolics and flavonoids were detected in some of the extracts